The Effect of Colchicine Administration on HsCRP Level and Mean Platelet Volume in Patients with Miocard Acute Infark - Wasyanto, Trisulo; Yasa, Ahmad; Murti, Bhisma (Indonesian Journal of Medicine, 2018)
Background: Patients with coronary heart disease (CHD) who have received standard therapy to the fullest, are still at risk for further cardiovascular events. This is likely because the standard therapy fails to inhibit some inflammatory pathways and platelet aggregation which implies the disease. This study aimed to determine the effect of colchicine on reducing levels of high sensitive c-reactive protein (HsCRP) and mean platelet volume (MPV) in patients with Acute Myocardial Infarction (IMA) in the Intensive Cardiovascular Unit (ICVCU) Dr. Moewardi Hospital, Surakarta.Subjects and Method: Experimental study was conducted with pre and post design. The study was conducted from November 1 to December 31, 2016. A sample of 32 patients with Acute Myocardial Infarction was divided into two groups. The control group was given a placebo and the treatment group was given colchicine 0.5 mg orally for 5 days. Statistical analysis was done using two mean different tests with dependent t-test or Mann-Whitney and two mean analysis paired using independent t-test or Wilcoxon.Results: The HsCRP delta level in colchicine group (mean = 3.82; SD = 2.20) was higher than control group (mean = 0.57; SD = 3.12) and it was statistically significant (p<0.001). The delta MPV levels in colchicine group (mean = 2.01; SD = 1.16) were higher than control group (mean = 0.64; SD = 0.83) and it was statistically significant (p = 0.001).Conclusion: The administration of 0.5 mg colchicine by oral for 5 days was associated with levels of HsCRP and MPV among IMA patients. Keywords: Colchicine, HsCRP, MPV, Acute Myocardial InfarctionCorrespondence: Trisulo Wasyanto. Department of Cardiology and Vascular Medicine, Faculty of Medicine, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta57126, Central Java, Indonesia. Email: trisulo.wasyanto@gmail.comIndonesian Journal of Medicine (2018), 162-167https://doi.org/10.26911/theijmed.2018.03.03.06